Early Relationships of a Low‐Energy Diet With Symptoms of Fibromyalgia. Issue 5 (2nd March 2022) - Stubbs, Aaron; Harte, Steve; Clauw, Daniel J.; Williams, David A.; McAfee, Jenna; Miller, Nicole; Brown, Megan; Med, Catherine Nay; Rothberg, Amy; Schrepf, Andrew
Abstract : Objective: Previous studies have demonstrated that weight loss has been shown to improve pain in weight‐bearing joints, and more recent studies suggest that weight loss may be accompanied by improvements in pain in non–weight‐bearing regions. In previous work, we demonstrated that these symptoms improve substantially in patients with obesity undergoing 12 weeks of a very low‐energy diet (VLED) restricted to 800 kcal as part of a weight‐loss program. Preclinical models also have shown analgesic effects of calorie restriction. The purpose of the current observational study was to determine the time course and trajectory of improvement in pain and other symptoms, especially during the early phase of a VLED intervention, prior to major weight loss. Methods: Participants were 195 individuals with obesity who had elevated levels of pain and associated symptoms at baseline (score of ≥4 on Fibromyalgia Survey Criteria) and completed a minimum of 3 weeks of a VLED intervention. The primary outcome was improvement in Fibromyalgia Survey Criteria at week 3. In secondary analyses, we created groups of those showing little/no improvement, moderate improvement, and high improvement (little/no improvement mean, 2.21; SD, 1.02; moderate improvement mean, 2.25; SD, 0.81; high improvement mean, 2.42; SD, 0.95; F2, 189  = 1.01, P  = 0.37), then compared baseline characteristics. Results: A large proportion of study participants (72%) experienced symptom reductions of 30% or greater by week 3, but there were no differences in the amount of weight lost at this time point. Those who showed little or no improvement (less than 30%) had a higher body mass index at baseline and were more likely to report a diagnosis of depression (both P  < 0.05). Conclusion: This degree of improvement after 3 weeks of a VLED is encouraging. These findings help establish the temporal pattern of symptom improvement associated with caloric restriction and suggest that the palliative effects of this diet are at least partly due to the diet itself, rather than the weight loss that ensues.